EVALUATION OF THE WIDELY-USED EQUATIONS OF HYDRAULIC LOSS CALCULATION AND CALIBRATION OF THE HAZEN-WILLIAMS EQUATION IN DRIP IRRIGATION LATERALS - Sh. Shafaei; Gh. Zarei; K. Ebrahimi; Sh. Soleimani; M. Shamsi (مهندسی عمران شریف)
Hazen-William’s equation is usually used to determine the hydraulic head loss when designing drip irrigation systems. The mentioned equation is suggested for pipes with diameters greater than 75 mm and flow rates above 2.3 l/s. However, lateral pipes with 16 to 32 mm diameters are generally used for trickle irrigation. In this case, the calculated hydraulic head loss is lower than the actual hydraulic head loss, and subsequently, the hydraulic pressure at the desired point will be lower than the required value. In other words, the output flow from the droppers will be reduced, and the water distribution uniformity will be less than expected. Herein, using laboratory models and polyethylene pipes with a diameter of 16, 20, 25, and 32 mm, the amount of hydraulic loss was measured for different flow rates and according to the permissible velocity limits. Hydraulic pressures were measured using a data logger, with one record for each second, and the discharge was adjusted volumetrically. A bypass pipe was installed on the physical model to control the discharge and the hydraulic pressure. The amount of hydraulic head loss was measured for different flow rates in the permissible flow velocity range (1-2 m/s). Then, by analyzing the recorded data, a new relationship was obtained that calculates the amount of hydraulic head loss in 16 to 32-mm pipes as a flow rate and pipe diameter function. The Hazen-Williams equation was compared with the results of Moody, Churchill, and Colebrook methods and the actual measured values. According to the results, the most significant error between the measured and the calculated head loss was for the Colebrook & White equation for the 25 mm pipe, and the smallest error was for the same equation for the 32 mm pipe. The obtained relationship is recommended for polyethylene pipes with a diameter of 16 to 32 mm and a Reynolds number above 2000 with high confidence. One of the advantages of the obtained relationship is its independence from the Hazen-Williams roughness coefficient and its remarkable accuracy.